Retroperitoneal Hematoma Following Enoxaparin Treatment in an Elderly Woman - A Case Report - Haq, MM; Taimur, SDM; Khan, SR; Rahman, MA (Cardiovascular Journal, 2010)
Retroperitoneal hematoma may occur as a result of trauma, rupture of arterial aneurysms (aortic or iliac), surgical complications, tumors and anticoagulation therapy. A life threatening retroperitoneal hemorrhage or hematoma is an infrequent complication of anticoagulation treatment. Enoxaparin is a low-molecular-weight heparin (LMWH) with several advantages over unfractionated heparin. Nevertheless, enoxaparin use is not without risk and severe retroperitoneal bleeding may occur following its use with a potentially fatal outcome. We report a case of sixty six years old female patient who develops a fatal retroperitoneal hematoma two days after enoxaparin treatment for acute coronary syndrome. Keywords: Retroperitoneal hematoma; Enoxaparin; Acute coronary syndrome. DOI: 10.3329/cardio.v3i1.6434 Cardiovasc. j. 2010; 3(1): 94-97